DAMPAK KEBAKARAN HUTAN GAMBUT TERHADAP SUBSIDENSI DI HUTAN TANAMAN INDUSTRI - Ratnaningsih, Ambar Tri; Prastyaningsih, Sri Rahayu (Wahana Forestra: Jurnal Kehutanan, 2017)
Forest fires in peat soils will affect hydrological characteristics and hydrological cycles. Industrial Plantation Forest in Riau Province is mostly located in peat soil. This study aims to measure the impact of forest fires on peat subsidence and water table level. The research location is located in industrial forest plantation located in Bengkalis Regency , Riau Province. The method of research is to install piezometer and iron rod stuck into the soil to penetrate the mineral soil layer, then the iron that appears on the surface of the soil is made permanent sign for reference in monitoring the altitude cha nge of the surrounding surface (subsidency). The fire peat forest has a depth of 12.21 cm month-1down water level from the peat surface while in the unburned area 10 cm month-1. In the burnt area the rate of peat surface decline is 0.159 cm month-1 while the unburned area is 0.119 cm month-1.